Post-Merger Cultural Integration and Customer Experience: An NLP Analysis of Indonesian Airport Reviews - Luthfi Octafian; Manahan Siallagan (Dinasti International Journal of Education Management And Social Science, 2025)
This study investigates the post-merger organizational culture integration of Indonesia’s state-owned airport operators, PT Angkasa Pura I and II, under the InJourney holding. It explores how core values are reflected in customer experience (CX) through digital feedback. Leveraging Natural Language Processing (NLP), the study analyzes 1,971 segmented review sentences derived from 619 user-submitted Google Maps reviews across six major airports. Reviews were classified by language and grouped into three time periods. Using lexicon-based sentiment scoring, CX dimension mapping, and cultural artifact detection linked to the AKHLAK core values, the analysis reveals that customers primarily discuss functional service aspects such as service quality, environment, and flow. Emotional and loyalty-related expressions were minimal. A decline in sentiment was observed in the post-merger phase, especially in ex-AP II airports. Cultural value mentions remained sparse and inconsistent. Statistical tests confirm significant differences across periods and regions, yet the impact of cultural integration on CX remains limited. These findings highlight the gap between internal cultural transformation efforts and external customer perceptions, offering methodological and managerial implications for monitoring public service transformation using big data analytics.